ESTUDIO DE LA INTERCONECTIVIDAD Y SEGURIDAD DE DATOS EN LA F.A.F.I - FONSECA BARRAGÁN, KEVIN ALEJANDRO (2018)
Currently, data security and interconnectivity go hand in hand, security procedures and technologies have been created to safeguard the integrity of data, but it can not be said that they are completely safe from intruders. Data security focuses on the protection of the infrastructure and all the information included in a computer. It can be said that the main characteristics of data security are: The integrity of the data. The Confidentiality. Availability. Jean François Carpentier says that data protection is essential, whatever its size, as soon as all the important information is stored in the infrastructure of your network. (Carpentier, 2016) In general terms what is interconnectivity is the communication of two or more networks, that using the network to the maximum we can share resources, access to shared databases. The faculty is made up of six careers that are Commercial Engineering, CPA, Systems Engineering, Information Systems Engineering, Accounting and Auditing, Commerce, where, over time, an academic platform was implemented in order to keep it safe and secure. access to data, thus streamlining academic processes which in past times did not impart confidence.